2016
DOI: 10.1038/ncomms13859
|View full text |Cite
|
Sign up to set email alerts
|

Cyst-Wall-Protein-1 is fundamental for Golgi-like organelle neogenesis and cyst-wall biosynthesis in Giardia lamblia

Abstract: The genome of the protozoan parasite Giardia lamblia is organized in two diploid nuclei, which has so far precluded complete analysis of gene function. Here we use a previously developed Cre/loxP-based knock-out and selection marker salvage strategy in the human-derived isolate WB-C6 to eliminate all four copies of the Cyst-Wall-Protein-1 locus (CWP1). Because these loci are silenced in proliferating trophozoites and highly expressed only in encysting cells, CWP1 ablation allows functional characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 54 publications
3
42
0
Order By: Relevance
“…CWP1 (Ebneter et al, 2016) was identified as differentially expressed by only one of the two methods of analysis we used, and was thus not included in the 475 differentially expressed genes (Materials and Methods). Through partitioning analysis and analysis of differential gene expression in the in vivo foci, we also identified six new cyst-specific proteins (Figure 5D and Supplemental Tables 7,8).…”
Section: Discussionmentioning
confidence: 99%
“…CWP1 (Ebneter et al, 2016) was identified as differentially expressed by only one of the two methods of analysis we used, and was thus not included in the 475 differentially expressed genes (Materials and Methods). Through partitioning analysis and analysis of differential gene expression in the in vivo foci, we also identified six new cyst-specific proteins (Figure 5D and Supplemental Tables 7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Given that CCVs have not been detected in Giardia , this begs the question of the functional role of a NECAP1 cardiolipin-binding orthologue in G. lamblia which was found to interact with G. lamblia AP2 subunits and Gl FYVE. Recent developments in gene knock-out [63] and CRISPR-Cas9-based knock-down [64, 65] methodologies tailored to G. lamblia will be instrumental towards a full functional characterization of Gl NECAP1’s function(s)…”
Section: Discussionmentioning
confidence: 99%
“…Given that CCVs have not been detected in Giardia, this begs the question of the functional role of a NECAP1 cardiolipin-binding orthologue in G. lamblia, which was found to interact with G. lamblia AP2 subunits and GlFYVE. Recent developments in gene knock-out [67] and CRISPR-Cas9-based knock-down [68,69] methodologies tailored to G. lamblia will be instrumental towards a full functional characterization of GlNE-CAP1's function(s).…”
Section: An Interactome-based Model For Pip-binding Proteins and Clatmentioning
confidence: 99%